2017
DOI: 10.1002/cpdd.328
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Bioavailability and Pharmacokinetic Comparability of Sirukumab Following Subcutaneous Administration by a Prefilled Syringe or an Autoinjector

Abstract: This phase 1, randomized, open-label study assessed the absolute bioavailability and pharmacokinetic comparability of sirukumab, a human anti-interleukin-6 monoclonal antibody, following subcutaneous (SC) administration via Prefilled Syringe-UltraSafe Passive® Delivery System (PFS-U) or Prefilled Syringe-SmartJect® Autoinjector (PFS-AI; Janssen Research & Development, LLC, Spring House, Pennsylvania). A total of 144 healthy male subjects were randomized to 5 single-dose treatment groups: sirukumab 50 mg and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…25 The estimated typical V/F of sirukumab was 16.1 L for patients with standard weights of 70 kg. After adjustment for SC bioavailability (around 81% to 95% 13 ), the volume of distribution of sirukumab was approximately 13 to15 L, close to the extracellular fluid compartment for a typical adult (ß14 L). This suggests that sirukumab has extravascular fluid distribution (such as interstitial synovial fluid) in addition to the vascular space (plasma volume of ß3 L).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The estimated typical V/F of sirukumab was 16.1 L for patients with standard weights of 70 kg. After adjustment for SC bioavailability (around 81% to 95% 13 ), the volume of distribution of sirukumab was approximately 13 to15 L, close to the extracellular fluid compartment for a typical adult (ß14 L). This suggests that sirukumab has extravascular fluid distribution (such as interstitial synovial fluid) in addition to the vascular space (plasma volume of ß3 L).…”
Section: Discussionmentioning
confidence: 99%
“…9 The reported absolute SC bioavailability of sirukumab ranged from 81% to 95%. 13 Here we present the results of a confirmatory population PK analysis based on sirukumab serum concentration data obtained from 4 phase 3 clinical trials for treating patients with moderately to severely active RA, SIRROUND −D, 14 −T, 10 −H 15 , and −M. 16 The objectives of this analysis were to describe the PK of sirukumab in RA patients and to quantify any intrinsic or extrinsic factors that may contribute significantly to the PK variability of sirukumab, and to obtain a robust population PK model that may facilitate further pharmacokinetic/pharmacodynamic (PK/PD) analysis.…”
mentioning
confidence: 99%
“…This box summarizes key points contained in the article. Comparison of prefilled syringes with vial/ampoule [11,15] or auto-injector [14,[16][17][18]. available [49].…”
Section: Article Highlightsmentioning
confidence: 99%
“…Using a single-dose, randomized, cross-over study design, Shafer et al [11] reported comparable PK and bioequivalence (90% CI for ratio of mean values of C max and AUC inf within the bound of 0.8-1.25) of moroctocog alfa for the treatment of hemophilia A when administered by prefilled syringe compared with traditional vials. Comparable PK and bioavailability have also been shown for SC administration by prefilled syringe, but relative to an autoinjector, for drugs such as belimumab [16] and ixekizumab [14] used in the treatment of systemic lupus erythematosus and plaque psoriasis, respectively, the interleukin-6 inhibitor sirukumab [18] and a pegylated form of recombinant granulocyte colony-stimulating factor, pegfilgrastim [17].…”
Section: Drug Characteristicsmentioning
confidence: 99%
“…The pharmacokinetics (PK) of sirukumab have been well characterized and were linear following single‐dose intravenous administration (0.03‐10 mg/kg) to healthy subjects or over a dose range of 25‐100 mg following single or multiple subcutaneous (SC) administration to healthy subjects or patients with RA . The reported absolute SC bioavailability of sirukumab ranged from 81%‐95% and the estimated terminal half‐life was approximately 17.4 days . Body weight and comorbid diabetes were identified as influential covariates on sirukumab PK, as patients who have higher body weight and/or comorbid diabetes tend to have lower exposure …”
mentioning
confidence: 99%